2009
DOI: 10.1007/s00395-009-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for preconditioning by the adenosine A1 receptor-selective agonist CCPA

Abstract: We have shown that the cellular process of macroautophagy plays a protective role in HL-1 cardiomyocytes subjected to simulated ischemia/reperfusion (sI/ R) (Hamacher-Brady et al. in J Biol Chem 281(40):29776-29787). Since the nucleoside adenosine has been shown to mimic both early and late phase ischemic preconditioning, a potent cardioprotective phenomenon, the purpose of this study was to determine the effect of adenosine on autophagosome formation. Autophagy is a highly regulated intracellular degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 33 publications
5
80
0
1
Order By: Relevance
“…A previous study showed that ischemic preconditioning induces autophagy formation and initiates cardioprotective effects against I/R injuries [15] . It has also been reported that pharmacological pretreatment with the adenosine A1 receptor selective agonist CCPA induces autophagy and confers cardioprotection against I/R injury [36] . In this previous study, the preconditioning was performed prior to the ischemic period and less damage occurred during the ischemic period [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that ischemic preconditioning induces autophagy formation and initiates cardioprotective effects against I/R injuries [15] . It has also been reported that pharmacological pretreatment with the adenosine A1 receptor selective agonist CCPA induces autophagy and confers cardioprotection against I/R injury [36] . In this previous study, the preconditioning was performed prior to the ischemic period and less damage occurred during the ischemic period [36] .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that pharmacological pretreatment with the adenosine A1 receptor selective agonist CCPA induces autophagy and confers cardioprotection against I/R injury [36] . In this previous study, the preconditioning was performed prior to the ischemic period and less damage occurred during the ischemic period [36] . After CCPA pre-treatment, diminished autophagy during simulated ischemia and reperfusion occurred because the cells experienced less stress, and less autophagy occurred as a response to reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Adult cardiac myocytes were prepared from 200 to 250 g male Sprague Dawley rats as previously described. 41 All animal procedures were in accordance with institutional guidelines and approved by the Institutional Animal Care and Use Committee. Briefly, the rat was anesthetized with sodium pentobarbital, the heart excised and rapidly cannulated via the aorta.…”
Section: Methodsmentioning
confidence: 99%
“…Autophagy is known to be activated during ischemic insult, but its contribution to neuronal death/survival is still being debated [16][17][18] . Recent reports also suggested an association between preconditioning and autophagy in both the heart and brain [19][20][21][22] . In an earlier study, we demonstrated that the neuroprotection induced by IPC is mediated by autophagy in a rat model of IPC, and the pharmacological induction of autophagy mimics the neuroprotection of IPC [23] .…”
Section: Introductionmentioning
confidence: 99%